PENGARUH METODE TREASURE CLUE TERHADAP KEAKTIFAN BELAJAR SISWA PADA PEMBELAJARAN IPAS MATERI RANTAI MAKANAN KELAS 4 SDK SANG TIMUR - Maria Ulfah; Bertilla Desilva Sare; Sufiana Quraninda; Syahril Romadhan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This article is motivated by research on the influence of the treasure clue method on the active learning of grade 4 students at SDK Sang Timur. The approach used in the research is a quantitative approach. Researchers used a pre-experimental design in the form of a one shot case study. Researchers took a sample of 20 students as an experimental class. The research results show that students' active learning using the treasure clue method is in the very good category with an average of 85%. So, there is a positive correlation between the treasure clue learning method and the active learning of class IV students. This shows that there is a positive and significant influence of the influence of the treasure clue learning method on students' active learning. Apart from that, students also showed an increase in better understanding of the concept of food chains. This method has proven to be effective in creating an interactive and fun learning atmosphere, so it is recommended to be applied to science learning.